Hubungan antara sikap dan minat pelajar, pengajaran guru dan rakan sebaya dengan pencapaian matematik pelajar-pelajar tingkatan empat - Abu Bakar, Zainuddin (Faculty of Education, 2008)
Mathematics is one of the most challenging subjects as perceived by some students. The purpose of this study was to investigate the relationship between several factors such as students' attitude, students' interest, teacher's instruction, peer influence and their mathematics achievement. Sample of this study involved 114 Form 4 (Grade10) students? selected from a public secondary school. The instrument used to elicit students' perception was a self reported questionnaire using the 5 point Likert-type scale. The findings showed that attitude of students, interest and strategy of teachers? teaching the subject had a positive association with students' achievement. Peer influence had a weak association with achievement in mathematics.